Pathophysiological relation between the systemic inflammation and the state of small airways in mild asthma with obesity - A. V. Yurenko; M. V. Antonyuk; E. E. Mineeva; K. K. Khodosova (Медицинская иммунология, 2022)
The aim of present study was to establish the relationship between the level of blood serum cytokines and indexes of pulmonary function as well as to identify the markers of evolving dysfunction of small airways in obese patients with partially controlled mild bronchial asthma. We have examined 53 patients with mild asthma of partially controlled clinical course complicated with obesity (I-II degree). The control group consisted of 25 healthy volunteers. All participants underwent spirometry, bodyplethysmography. Tumor necrosis factor alpha (TNFα), interferon gamma (IFNγ), interleukins (IL) IL2, IL-4, IL-6, IL-10, IL-17A were determined in blood serum. In the patients with partially controlled mild asthma, an increase in IL-17A by 55.8%, and IL-4 by 44.9% was detected, regardless of body mass. According to the results of cluster analysis, two sub-groups were discerned, depending on the state of the small airways and the levels of pro- and anti-inflammatory cytokines. The dysfunction of small airways was shown to be accompanied by hypercytokinemia being more common in bronchial asthma with predominant Th1-and Th17-immune responses. We have revealed an association between IL-17A, IL-6 levels and functional indices reflecting the state of the small airways, as well as correlation between IFNγ and the indices of bronchial obstruction. The features of pulmonary function were found to be dependent on the cytokine status in mild asthma with obesity. Two immuno-functional variants were identified, differing in activity of systemic inflammation, type of immune response, and functional state of the small airways. The revealed relationships allow us to consider IL-17A, IL-6 and IFNγ as markers of small airways dysfunction in mild asthma of partially controlled clinical course associated with obesity.